Direct comparison of oscillatory activity in the motor system of Parkinson's disease and dystonia: A review of the literature and meta-analysis. Issue 6 (June 2019) - Piña-Fuentes, D.; van Dijk, J.M.C.; Drost, G.; van Zijl, J.C.; van Laar, T.; Tijssen, M.A.J.; Beudel, M.
Highlights: The distribution of low-frequency (LF) and beta oscillatory power differs between Parkinson's disease (PD) and dystonia. Increased LF power is present in subcortical local field potentials (LFPs) of dystonia when compared to PD. Increased beta power is present in subcortical LFPs of PD when compared to dystonia. Abstract: Objective: To outline the current knowledge of (sub)cortical oscillations in Parkinson's Disease (PD) and dystonia, and to quantitatively summarize the results of direct comparisons of local oscillatory power between both diseases in the resting state, without medication or stimulation, in both the low-frequency (LF, ±4–12 Hz) and beta (±13 to ∼30 Hz) range. Methods: Eight relevant studies were included. Recordings from 127 dystonia-, and 144 PD-patient hemispheres were analyzed. Ratios of LF and beta power between diseases were obtained. Results: Beta oscillations in dystonia were lower when compared to beta oscillations in PD, ratio = 0.72, Z = 3.56, p = 0.0004, 95% CI [0.60, 0.86]. Subgroup analyses showed significant differences only in the GPi, whilst conflicting evidence was shown in the STN. LF oscillations in PD were lower when compared to LF oscillations in dystonia, ratio = 0.77, Z = 2.45, p = 0.01, 95% CI [0.63, 0.95]. Subgroup analyses showed significant differences in the GPi and the STN, but not in the M1. Conclusions: LF and beta oscillations are present in the resting-state motor network of both PD and dystonia patients. However, the power distribution of those oscillations differs between diseases. Significance: This meta-analysis provides high-level evidence which supports the presence of exaggerated oscillations across the parkinsonian/dystonic motor networks.